Platinum anniversary – 70 years of highlights and influences of the World Federation of Occupational Therapists. Issue 1 (2nd January 2022) - Pattison, M.; McKinstry, C.; Cox, D.; Boniface, G.; McLennan, N.
ABSTRACT: The World Federation of Occupational Therapists (WFOT) was inaugurated in 1952 (Paterson, C. F. (1994). The First International Congress of the World Federation of Occupational Therapists—Edinburgh, 1954. British Journal of Occupational Therapy, 57(4), 116–120) and celebrates its 70th anniversary in 2022. The last 70 years have seen the growth and development of occupational therapy globally, with WFOT growing from 10 to 105 member organisations. While the important core principle of occupational activity (occupations) in our daily lives has remained constant in those 70 years, the approach, and how we do them has changed. As occupational therapists we have continued to adapt and change to meet the needs of the societies and cultures in which we work. The primary aim of this paper is to share some of the major highlights of the past 70 years, outlining the influences as reflected in the ongoing business of WFOT.